Loyalitas Kesukuan dalam Pemilu 1992 di Kotamadya Pematang Siantar - SITUMORANG, TONNY P.; HARAHAP, HUSNUL ISA (Politeia: Jurnal Ilmu Politik, 2016)
According to R William Liddle, the 1955 election was marked by a pattern-based tribal party support (primordial identities).This theory has raised the question whether the pattern will persist in the next election.Especially in the Kota PematangSiantar (where the research was conducted).This study has tried to answer these questions. The focus on the relationship between tribal loyalties to political parties (PPP, PDI, Golkar) concerning the election in the KotamadyaPematangSiantar 1992. The findings of this study indicate thevariables of tribal loyalty does not clearly describe a causal relationship with the behavior of voters. This means that there are patterns of party choice based on ethnicity. But the relationship is not as strong as in 1955.In the 1992 election not all political parties based on tribal support, except PPP and PDI. Mostly supporters of PDI is the tribe Batak Tapanuli Utara and PPP is supported by the tribe Batak Tapanuli Selatan. In terms of religion, PPP supporters almost entirely Muslim. Meanwhile, supporters of PDI predominantly Christian. However, in contrast with the two parties, the Golkar Party supported by the community with a wide-variety of tribes (Batak Tapanuli Utara, Batak Tapanuli Selatan, Jawa, Simalungun, Karo, etcetera). The party also supported by voters who have a different religion (includingMuslim and Christian voters). This study was conducted with the political behavioral approach.The research method using descriptive methods. Collecting data with field research techniques. Analysis using descriptive analysis. Keywords: Election, Tribal loyalties, Political parties.